2016
DOI: 10.1386/ctl.11.2.157_1
|View full text |Cite
|
Sign up to set email alerts
|

Is Student Union a tokenism of student participation in school governance?

Abstract: This article is a report on part of a larger research on student participation in school governance in the Hong Kong context. It addresses the question ‘Is the Student Union a tokenism of student participation in school governance in the context of Hong Kong?’. The research adopts a mixed methodology comprising both quantitative and qualitative methods. For the quantitative study, 3209 valid student questionnaires from 51 secondary schools of different backgrounds were collected. For the qualitative study, fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…The most prominent factors lay in the school's context. Aside from a single study (Burger, 2019), all the studies that explored how students' rights consciousness differs across schools indicated that the school context matters, particularly its rights-based practices (e.g., Banerjee et al, 2018;Birnhack & Perry-Hazan, 2020;Hart et al, 2001;Kaba, 2000;Khoury-Kassabri & Ben-Arieh, 2009;Leung et al, 2016;Preiss et al, 2016) and the diversity of the student body and school staff (Assari, 2018;Benner & Graham, 2011;Brown & Chu, 2012;Closson et al, 2014;Leath et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most prominent factors lay in the school's context. Aside from a single study (Burger, 2019), all the studies that explored how students' rights consciousness differs across schools indicated that the school context matters, particularly its rights-based practices (e.g., Banerjee et al, 2018;Birnhack & Perry-Hazan, 2020;Hart et al, 2001;Kaba, 2000;Khoury-Kassabri & Ben-Arieh, 2009;Leung et al, 2016;Preiss et al, 2016) and the diversity of the student body and school staff (Assari, 2018;Benner & Graham, 2011;Brown & Chu, 2012;Closson et al, 2014;Leath et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Other than a single qualitative study of young students in Sweden (Quennerstedt, 2016), the literature consistently shows that students tend to criticize the limited scope of participation rights in school (Allan & Ianson, 2004;Geldenhuys & Doubell, 2011;McCluskey et al, 2013;Osler, 2000). However, studies of student council participants indicated that despite the trivial nature of the matters they decided, these students were generally positive about their experience (Kaba, 2000;Leung et al, 2016). One of these studies explored the perceptions of students who participated in Chicago school councils, which included student representatives under the Chicago School Reform Act (Kaba, 2000).…”
Section: School Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve this, students are expected to be rule abiding and not to challenge authority. In other words, from an early stage of studying students are taught to be personally responsible citizens with the emphasis on being obedient and law abiding (Leung et al, 2016). They are not granted much freedom to participate in school affairs lest they abuse that freedom, which it is feared will result in a loss of control, as stated before.…”
Section: Student Participation In School Governancementioning
confidence: 99%
“…In addition, due to the overprotective nature of some teachers, they do not empower students to participate in school governance. Some research shows that there are teachers who interpret children's immaturity as an inability to be rational and that they need protecting by adults (Leung et al, 2016), which extends to making decisions for them whether that be trivial matters or school managerial domains. They are concerned that children would not be able to accept the consequences of making wrong decisions.…”
Section: Student Participation In School Governancementioning
confidence: 99%